2012
DOI: 10.1093/nar/gks871
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transitions regulate the exposure of a DNA-binding domain in the RuvBL1–RuvBL2 complex

Abstract: RuvBL1 and RuvBL2, also known as Pontin and Reptin, are AAA+ proteins essential in small nucleolar ribonucloprotein biogenesis, chromatin remodelling, nonsense-mediated messenger RNA decay and telomerase assembly, among other functions. They are homologous to prokaryotic RuvB, forming single- and double-hexameric rings; however, a DNA binding domain II (DII) is inserted within the AAA+ core. Despite their biological significance, questions remain regarding their structure. Here, we report cryo-electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 34 publications
10
79
0
1
Order By: Relevance
“…Purified HisRuvBL1 was resolved as a mixture of oligomers and free subunits, whereas His-RuvBL2 did not oligomerize under our experimental conditions. On the other hand, His-RuvBL1-RuvBL2 and RuvBL1-RuvBL2 formed hetero-oligomeric complexes with an approximate 1:1 ratio that we interpreted as hexamers and dodecamers based on previous information (27). We found that Strep-II-YY1 interacted with His-RuvBL1 but not His-RuvBL2 under our experimental conditions after pulling down the Strep-II tag and eluting the retained His-RuvBL1 or His-RuvBL2 with D-desthiobiotin (Fig.…”
Section: Yy1 Multimerizes By the Association Of Dimers-supporting
confidence: 56%
See 3 more Smart Citations
“…Purified HisRuvBL1 was resolved as a mixture of oligomers and free subunits, whereas His-RuvBL2 did not oligomerize under our experimental conditions. On the other hand, His-RuvBL1-RuvBL2 and RuvBL1-RuvBL2 formed hetero-oligomeric complexes with an approximate 1:1 ratio that we interpreted as hexamers and dodecamers based on previous information (27). We found that Strep-II-YY1 interacted with His-RuvBL1 but not His-RuvBL2 under our experimental conditions after pulling down the Strep-II tag and eluting the retained His-RuvBL1 or His-RuvBL2 with D-desthiobiotin (Fig.…”
Section: Yy1 Multimerizes By the Association Of Dimers-supporting
confidence: 56%
“…In the indicated cases, SEC was performed using a Superdex 200 PC 3.2/30 (GE Healthcare) or Superdex 200 10/300 GL (GE Healthcare) column equilibrated in 50 mM Tris-HCl, pH 7.4, 250 mM NaCl, 10% (v/v) glycerol. His-RuvBL1-RuvBL2 and RuvBL1-RuvBL2 were produced as described (27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we show here that cells reconstituted with the Reptin Walker B mutants expressed normal levels of Pontin such as those reconstituted with WT siRNA-resistant Reptin (20), thus ruling out that some of the effects seen with the mutants might be due to the loss of Pontin. Although the issue is not completely settled, the most recent evidence suggests that human Reptin and Pontin are organized in heterohexamers (24)(25)(26). It is thus likely that, when expressed in the presence of endogenous Reptin and Pontin, Walker B mutants will replace WT Reptin within hexamers and can thus exert a dominant negative effect.…”
Section: Discussionmentioning
confidence: 99%